IMPLEMENTASI KEBIJAKAN PENGEMBANGAN RUANG TERBUKA HIJAU SEMPADAN PANTAI DI KOTA CIREBON PROVINSI JAWA BARAT - Cut Novisar Syahfitri (Fakultas Politik Pemerintahan IPDN, 2020)
This study aims to determine and describing the implementation of the development of Coastal Green Open Space and the factors that cause the ineffective implementation of the policy. This research focused on policy implementation of spatial plans in development of urban areas which based by theory of Charles O. Jones: organizations, interpretation, and application. The author using descriptive qualitative research method with an inductive approach. The data were collected through observation, interviews, and documentation. While the data were analyzed with data analysis, data presentation, and conclusion. The research data were analyzed using data analysis techniques, data presentation, and drawing conclusion. The results showed that the implementation process of the regional spatial planning policy in the development of green open space on the coastline of Cirebon City was not implemented properly. The main factor that causes the ineffective implementation of the policy is that the interpretation of the policy it self is vary, so that it affects the implementation of the policy. Suggested to the Cirebon City Government needs to support and be committed to implementing a coastal border green open space development policy and the Cirebon City Government needs to be prepared to face every possibility and challenge of problems that arise and become obstacles in the implementation of the development policy of coastal green open space.Keywords: Implementation, Open Green Space Boundary Beach